Raising Environmental Awareness in School: A Case Study of Environmental Education Through Implementation Adiwiyata-based Curriculum - Riezky Maya Probosari; Febriani Sarwendah Asri Nugraheni; Fatma Widyastuti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
The Adiwiyata school project is a program of the Indonesian Ministry of the Environment which aims to make school members responsible for protecting and managing the environment by way of good school governance to encourage sustainable development. This research was conducted to determine the understanding and environmental awareness of the secondary school community in Central Java, Indonesia,  held in one junior high school and one senior high school in Semarang Regency that is applying to become Adiwiyata schools at the national level.  The participants were 49 teachers and 60 students from the two schools, had been tested their environmental knowledge through questionnaires regarding the implementation of the Adiwiyata-based curriculum and its impact on environmental attitudes and scientific attitudes of students. Structured interviews were also conducted to dig deeper into the problems and solutions made by teachers related to the Adiwiyata project. The results showed that most teachers had tried to incorporate environmental elements into their learning tools, both in the form of assessment instruments and the media. Meanwhile, it was found that the level of environmental awareness of students was classified as high, especially among female students. Follow-up research that refers to optimizing environmental awareness through learning strategies and media is immediately carried out.